2015
DOI: 10.1080/10962247.2015.1106991
|View full text |Cite
|
Sign up to set email alerts
|

Projected ozone trends and changes in the ozone-precursor relationship in the South Coast Air Basin in response to varying reductions of precursor emissions

Abstract: Results of this study indicate that ozone levels in the western and central SoCAB would remain the same or increase with even a relatively small shortfall in the projected NOx reductions under planned NOx-focused controls. This possibility, therefore, warrants a rigorous analysis of the costs and effects of varying reductions of VOC and NOx on the formation and combined health impacts of ozone and secondary particles. Given the nonlinearity of ozone formation, such analyses should include the implications of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…The SEARCH-observed afternoon slope values of ∼ 5 : 1 prior to 2003-2007 are comparable to, or lower than, similar regression results obtained in studies during the 1990s -which showed observed summer slope values of 11 : 1 in rural Georgia in 1991 (Kleinman et al, 1994); 8.5 : 1 at rural eastern sites (Trainer et al, 1993); 7 : 1 near Birmingham, AL, in 1992(Trainer et al, 1995; 5.7 : 1 near Nashville, TN, in 1995(Sillman et al, 1998; and 4.7 : 1 near Nashville, TN, in 1999(Zaveri et al, 2003 -and to modeling results and observations with composite regression slope values of 6.7 and 7.6, respectively, within the afternoon planetary boundary layer in the eastern US during the summer of 2002 (Godowitch et al, 2011). The SEARCH regression slope values prior to 2003-2007 are, as expected, higher than other 1990s values that were corrected for deposition losses, which, for example, yielded adjusted estimated values between 3 : 1 and 5 : 1 near Nashville in 1995 St.…”
Section: Comparisons With Observational and Modeling Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…The SEARCH-observed afternoon slope values of ∼ 5 : 1 prior to 2003-2007 are comparable to, or lower than, similar regression results obtained in studies during the 1990s -which showed observed summer slope values of 11 : 1 in rural Georgia in 1991 (Kleinman et al, 1994); 8.5 : 1 at rural eastern sites (Trainer et al, 1993); 7 : 1 near Birmingham, AL, in 1992(Trainer et al, 1995; 5.7 : 1 near Nashville, TN, in 1995(Sillman et al, 1998; and 4.7 : 1 near Nashville, TN, in 1999(Zaveri et al, 2003 -and to modeling results and observations with composite regression slope values of 6.7 and 7.6, respectively, within the afternoon planetary boundary layer in the eastern US during the summer of 2002 (Godowitch et al, 2011). The SEARCH regression slope values prior to 2003-2007 are, as expected, higher than other 1990s values that were corrected for deposition losses, which, for example, yielded adjusted estimated values between 3 : 1 and 5 : 1 near Nashville in 1995 St.…”
Section: Comparisons With Observational and Modeling Studiesmentioning
confidence: 79%
“…Observed O 3 extrema can also exhibit an apparent linear or near-linear response to ambient NO x mixing ratios if the extrema consistently fall within the lower-right quadrant (NO x -sensitive 8186 C. L. Blanchard and G. M. Hidy: Ozone response to emission reductions in the southeastern US regime) of an O 3 -VOC-NO x diagram, a concise graphical representation first established empirically from southern California data and later generated using the Empirical Kinetic Modeling Approach (EKMA) (illustrated in Hidy and Blanchard, 2015). The O 3 -VOC-NO x diagram has been adopted by many investigators for displaying the output of box models (e.g., Fujita et al, 2003Fujita et al, , 2015 and grid-based photochemical models (e.g., Reynolds et al, 2003Reynolds et al, , 2004.…”
Section: National O 3 Response To Emission Reductionsmentioning
confidence: 99%
“…The South Coast Air Quality Management District (SCAQMD) has the responsibility for implementing control measures to bring the region into compliance with the NAAQS. Stringent controls on VOC and NO x emissions over the last 5 decades have resulted in a dramatic improvement in ozone levels in the SoCAB [7,8]. Although the 2008 NAAQS is still exceeded in the Basin on many summer days, the year-to-year ozone reductions have been significant.…”
Section: Introductionmentioning
confidence: 99%
“…Atmosphere 2017, 8,145 6 of 25 measured values [23], with a small bias towards under-prediction. While the overall operational evaluation showed reasonable model performance, the ability of the modeling system to accurately predict responses to changes in emissions was not tested.…”
Section: The 2012 Aqmp and 2016 Aqmp Modelingmentioning
confidence: 99%
See 1 more Smart Citation